Modified polymeric binder for metallurgical pellets and method for its preparation

CN122898730APending Publication Date: 2026-10-13CHANGZHI XUANRUI IND & TRADE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511193380.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]然而,现有常用的球团粘结剂在实际应用中仍面临诸多挑战:如膨润土粘结剂的添加量高会引入大量无效矿物成分,降低球团铁品位;有机粘结剂虽然不会降低球团铁品位,但有机粘结剂的粘结强度、特别是高温阶段的热稳定性和在高盐分矿种中的耐盐性常常不足,导致生球强度不够或焙烧前期强度损失过快,许多有机粘结剂在初始升温阶段(300-600℃)内过早降解,失去粘结作用,影响球团矿的最终强度

Benefits of technology

[0023]本发明通过在羧甲基纤维素钠骨架上引入高反应活性的马来酰亚胺基团,再通过巯基与马来酰亚胺基团发生特异性的点击反应,从而引入功能性聚合物侧链,并且反应形成的硫代琥珀酰亚胺键是强共价键,具有优异的化学稳定性,确保了接枝上的聚合物侧链牢固地锚定在羧甲基纤维素钠主链上,不易在后续加工中发生水解或断裂脱落,保证了改性效果的持久性,该键本身也具有较好的热稳定性,有助于粘结剂整体结构在升温过程中保持完整。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a modified polymer binder special for metallurgical pellets and a preparation method thereof, and belongs to the technical field of pellet production. The binder is composed of the following components in parts by mass: sodium-based montmorillonite 50-60 parts, grafted modified sodium carboxymethyl cellulose 10-20 parts, corn starch 3-5 parts, sodium alginate 3-5 parts, and sodium humate 2-4 parts. After the sodium carboxymethyl cellulose is maleimide, polymer side chains are introduced through mercapto click reaction, forming a strong covalent bonding thiosuccinimide bond, ensuring that the side chains are firmly anchored, and having excellent thermal stability. The hydrophobic association of the cashew phenol alkyl long chain cooperates with the quaternary ammonium salt cationic group, neutralizes the excess negative charge, resists the charge shielding effect under high ion yellow, increases the solution viscosity and improves the temperature resistance. The rigid structure of oleanolic acid pentacyclic triterpene is introduced as a high-thermal-stability node, limiting the thermal motion of the molecular chain, delaying the degradation process, so that the binder maintains the binding effect in the initial stage of roasting, and reduces the loss of pellet strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of pellet production technology, and particularly relates to a modified polymer binder for metallurgical pellets and its preparation method. Background Technology

[0002] Pelletizing is a key processing step in producing finely ground materials into pellets that meet specific metallurgical requirements. The main process includes: preparing raw materials such as ore powder and binders, mixing them according to a set ratio, adjusting the moisture content, and then rolling and binding the materials into green pellets in a pelletizing machine. These green pellets are then roasted at high temperatures to obtain pellets with good metallurgical properties (such as high strength, high reducibility, and low expansion rate). The widespread application of iron ore pelletizing effectively fills the resource gap caused by the depletion of rich ore resources, transforming fine-grained iron concentrate, which was originally difficult to feed directly into furnaces, into high-quality feedstock for blast furnaces or direct reduction furnaces, meeting the growing demand of modern metallurgical industry for high-quality, homogeneous furnace feed.

[0003] In the actual pellet production process, binders are indispensable core additives. Their performance has a decisive impact on many key factors, including the formation process of green pellets (pelletization, green pellet strength, particle size distribution), the drying behavior of green pellets, the roasting and consolidation process, and the final physical strength (compressive strength, drop strength) and metallurgical properties of the pellets. Therefore, screening and developing high-performance binders is one of the core measures to optimize pellet production process parameters and improve the overall quality and stability of pellets. The main mechanisms of binders in the pelletizing process of iron concentrate include: (1) improving the bonding performance between iron concentrate particles in water-bearing bodies. After absorbing water, they exhibit colloidal properties, which promote the formation of green pellets and improve their initial strength by enhancing the molecular adhesion, hydrogen bonding and capillary forces between particles; (2) binders usually have a large specific surface area and excellent water absorption capacity. During the pelletizing process, they can adsorb and stabilize an appropriate amount of water, which helps to reduce the water content required by the actual mixture, stabilize the pelletizing process of iron concentrate, accurately control the growth rate and particle size distribution of green pellets, reduce the phenomenon of excessive moisture or dryness, and ensure the stability of pelletizing operations; (3) during the preheating and initial high temperature stage of pellet roasting, some binder components or decomposition products can temporarily maintain or enhance the connection between particles, which helps to resist thermal stress, reduce crack generation, and indirectly contribute to the strength of the final pellet ore.

[0004] However, existing commonly used pellet binders still face many challenges in practical applications: for example, high addition of bentonite binders can introduce a large amount of ineffective mineral components, reducing the iron grade of the pellets; while organic binders do not reduce the iron grade of the pellets, their bonding strength, especially their thermal stability at high temperatures and their salt resistance in high-salt minerals, are often insufficient, leading to insufficient green pellet strength or excessively rapid strength loss in the early roasting stage. Many organic binders degrade prematurely in the initial heating stage (300-600℃), losing their bonding effect and affecting the final strength of the pellets. Therefore, developing a new composite binder with excellent bonding performance, stable structure, good high-temperature resistance, strong salt resistance, and minimal impact on the iron grade of the pellets is of great significance for improving the quality of pellets. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a novel composite binder with excellent bonding performance, stable structure, good high temperature resistance, strong salt resistance and little impact on the iron content of pellets.

[0006] To achieve the above objectives, the following technical solution is adopted: This invention provides a modified polymer binder for metallurgical pellets, comprising the following components in parts by weight: 50-60 parts of sodium montmorillonite, 10-20 parts of grafted modified sodium carboxymethyl cellulose, 3-5 parts of corn starch, 3-5 parts of sodium alginate, and 2-4 parts of sodium humate.

[0007] Of the above components, sodium montmorillonite provides excellent water absorption and swelling properties, ion exchange capacity and basic bonding strength; corn starch and sodium alginate, as natural polymer binders, provide viscosity and water retention; sodium humate provides protection and a certain ion exchange capacity; and grafted modified sodium carboxymethyl cellulose significantly improves the overall bonding strength, temperature resistance and salt resistance of the system.

[0008] Furthermore, the grafted modified sodium carboxymethyl cellulose is prepared through the following steps:

[0009] S1. Under nitrogen protection, sodium carboxymethyl cellulose was dispersed in N,N-dimethylformamide and stirred at room temperature for 2 hours. Then, 3-maleimide propionic acid, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added in sequence. The mixture was heated to 50-55℃ and reacted for 12 hours. The reaction solution was cooled to room temperature, filtered, and the filtrate was poured into anhydrous ethanol to precipitate. The precipitate was washed three times each with ethanol and water and dried to obtain maleimide-modified sodium carboxymethyl cellulose.

[0010] S2. Maleimide-modified sodium carboxymethyl cellulose is added to N,N-dimethylformamide, followed by ethylenediaminetetraacetic acid and a polymer modifier. The pH is adjusted to 6.5-7.0 with 0.1 mol / L hydrochloric acid or 0.1 mol / L sodium hydroxide solution. The reaction is carried out for 16-24 hours. Then the solvent is removed, the mixture is washed three times with ethanol, and dried to obtain the grafted modified sodium carboxymethyl cellulose.

[0011] Furthermore, the polymer modifier is prepared by the following steps:

[0012] (1) Dissolve 2-mercapto-1H-benzimidazole-5-carboxylic acid and cashew phenol in tetrahydrofuran, add 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, react at 50-60℃ for 12-18h, filter to remove the precipitate, add bromohexane to the filtrate, heat to 76-80℃ and react for 24-36h, remove the solvent, recrystallize the residue three times with a mixed solution of ethyl acetate and n-hexane in a volume ratio of 1:3, and dry to obtain cashew phenol quaternary ammonium salt monomer;

[0013] (2) Using an oil-water separation device, hydroxyethyl methacrylate and carboxypropyl oleanolic acid were added to toluene, mixed evenly, and then p-toluenesulfonic acid and hydroquinone were added. The mixture was refluxed for 12-18 hours. The reaction solution was then cooled to room temperature. The organic phase was washed three times each with 5% sodium bicarbonate solution and deionized water to remove the solvent. After drying, the modified oleanolic acid monomer was obtained.

[0014] (3) Under nitrogen protection, cashew phenol quaternary ammonium salt monomer, oleanolic acid modified monomer and sulfonic acid unsaturated monomer are added to N,N-dimethylformamide, mixed evenly and then azobisisobutyronitrile is added. The reaction is carried out at 65-70℃ for 8-12h. The reaction solution is then cooled to room temperature and poured into acetone to precipitate. The precipitate is washed with acetone 3 times and dried to obtain the polymer modifier.

[0015] Further, in step S1, the feeding ratio of sodium carboxymethyl cellulose, 3-maleimide propionic acid, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and N,N-dimethylformamide is 100g: 20-30g: 25-35g: 2-5g: 600-1000mL.

[0016] Furthermore, in step S1, the feeding ratio of maleimide-modified sodium carboxymethyl cellulose, ethylenediaminetetraacetic acid, polymer modifier, and N,N-dimethylformamide is 100g: 2-5g: 30-50g: 800-1500mL.

[0017] Further, in step (1), the feeding ratio of 2-mercapto-1H-benzimidazole-5-carboxylic acid, cashew phenol, 4-dimethylaminopyridine, N,N-dicyclohexylcarbodiimide, bromohexane and tetrahydrofuran is 55g: 62-68g: 1.5-2.5g: 25-30g: 20-25g: 400-600mL.

[0018] Further, in step (2), the feeding ratio of hydroxyethyl methacrylate, carboxypropyl oleanolic acid, p-toluenesulfonic acid, hydroquinone and toluene is 40g: 65-72g: 1.5-1.8g: 0.2-0.5g: 320-350mL.

[0019] Furthermore, in step (3), the feeding ratio of cashew phenol quaternary ammonium salt monomer, oleanolic acid modified monomer, sulfonic acid unsaturated monomer, azobisisobutyronitrile and N,N-dimethylformamide is 30g: 3-8g: 25-30g: 1.2-1.5g: 300-400mL.

[0020] Furthermore, the sulfonic acid unsaturated monomer is selected from one of 2-acrylamido-2-methylpropanesulfonic acid, 3-acrylamidopropanesulfonic acid, or 2-(methacryloyloxy)ethanesulfonic acid.

[0021] Furthermore, the preparation method of the metallurgical pellet-specific modified polymer binder includes: mixing sodium montmorillonite, grafted modified sodium carboxymethyl cellulose, corn starch, sodium alginate and sodium humate evenly, and then drying, crushing and grinding to obtain the metallurgical pellet-specific modified polymer binder.

[0022] The beneficial effects of this invention are:

[0023] This invention introduces highly reactive maleimide groups onto the sodium carboxymethyl cellulose backbone, and then introduces functional polymer side chains through a specific click reaction between the thiol groups and the maleimide groups. The thiosuccinimide bonds formed in the reaction are strong covalent bonds with excellent chemical stability, ensuring that the grafted polymer side chains are firmly anchored to the sodium carboxymethyl cellulose backbone and are not prone to hydrolysis or breakage during subsequent processing, thus ensuring the durability of the modification effect. The bond itself also has good thermal stability, which helps the overall structure of the binder to remain intact during heating.

[0024] Cashew phenol alkyl long chains have a significant hydrophobic association effect, which can effectively compensate for the electrostatic repulsion caused by the excessive negative charge density on the sodium carboxymethyl cellulose molecular chain, promote the appropriate aggregation and network formation of molecular chains in solution. The quaternary ammonium salt cationic groups can not only partially neutralize the negative charge, weaken the charge shielding effect and double layer compression in a high ionic strength environment, but also make the molecular chain more stretchable, significantly increasing its hydrodynamic volume and solution viscosity. At the same time, the synergistic effect of the long-chain hydrophobic groups and the quaternary ammonium salt also provides good temperature resistance.

[0025] Oleanolic acid is a pentacyclic triterpenoid compound with a fused ring structure that exhibits high thermal stability and rigidity. Introducing it into the polymer side chain introduces a rigid node with high thermal stability into the molecular chain. This not only results in a high thermal decomposition temperature but also effectively restricts the thermal motion of the sodium carboxymethyl cellulose backbone and polymer side chains, delaying the thermal degradation process of the molecular chain and significantly improving the thermal stability of the entire binder molecule. This allows it to maintain its binding effect for a longer period during the initial stage of pellet calcination, reducing strength loss. The introduction of the rigid structure also helps to increase the molecular weight and the structural viscosity of the solution. Detailed Implementation

[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.

[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the experimental materials used in the following examples are all purchased from commercial channels.

[0029] Example 1: A modified polymer binder for metallurgical pellets, comprising the following components in parts by weight: 50 parts sodium montmorillonite, 10 parts grafted modified sodium carboxymethyl cellulose, 3 parts corn starch, 3 parts sodium alginate, and 2 parts sodium humate.

[0030] The preparation method of the metallurgical pellet-specific modified polymer binder is as follows: the sodium-based montmorillonite, grafted modified sodium carboxymethyl cellulose, corn starch, sodium alginate and sodium humate are mixed evenly, and then dried, crushed and ground to obtain the metallurgical pellet-specific modified polymer binder.

[0031] The grafted modified sodium carboxymethyl cellulose is prepared through the following steps:

[0032] S1. Under nitrogen protection, 100g of sodium carboxymethyl cellulose was dispersed in 600mL of N,N-dimethylformamide and stirred at room temperature for 2h. Then, 20g of 3-maleimide propionic acid, 25g of N,N-dicyclohexylcarbodiimide and 2g of 4-dimethylaminopyridine were added in sequence. The mixture was heated to 50℃ and reacted for 12h. The reaction solution was cooled to room temperature, filtered, and the filtrate was poured into anhydrous ethanol to precipitate. The precipitate was washed three times each with ethanol and water and dried to obtain sodium maleimide-modified carboxymethyl cellulose.

[0033] S2. Add 100g of maleimide-modified sodium carboxymethyl cellulose to 800mL of N,N-dimethylformamide, then add 2g of ethylenediaminetetraacetic acid and 30g of polymer modifier. Adjust the pH to 6.5 with 0.1mol / L hydrochloric acid or 0.1mol / L sodium hydroxide solution, react for 16h, then remove the solvent, wash three times with ethanol, and dry to obtain the grafted modified sodium carboxymethyl cellulose.

[0034] The polymer modifier is prepared by the following steps:

[0035] (1) Dissolve 55g of 2-mercapto-1H-benzimidazole-5-carboxylic acid and 62g of cashew phenol in 400mL of tetrahydrofuran, add 1.5g of 4-dimethylaminopyridine and 25g of N,N-dicyclohexylcarbodiimide, react at 50℃ for 12h, filter to remove the precipitate, add 20g of bromohexane to the filtrate, heat to 76℃ and react for 24h, remove the solvent, recrystallize the residue three times with a mixed solution of ethyl acetate and n-hexane in a volume ratio of 1:3, and dry to obtain cashew phenol quaternary ammonium salt monomer;

[0036] (2) Using an oil-water separation device, 40g of hydroxyethyl methacrylate and 65g of oleanolic acid carboxypropyl ester were added to 320mL of toluene. After mixing evenly, 1.5g of p-toluenesulfonic acid and 0.2g of hydroquinone were added. The mixture was refluxed for 12h. The reaction solution was then cooled to room temperature. The organic phase was washed three times each with 5% sodium bicarbonate solution and deionized water to remove the solvent. After drying, the modified oleanolic acid monomer was obtained.

[0037] (3) Under nitrogen protection, 30g of cashew phenol quaternary ammonium salt monomer, 3g of oleanolic acid modified monomer and 25g of 2-acrylamido-2-methylpropanesulfonic acid were added to 300mL of N,N-dimethylformamide, mixed evenly and then 1.2g of azobisisobutyronitrile was added. The reaction was carried out at 65℃ for 8h. The reaction solution was then cooled to room temperature and poured into acetone to precipitate. The precipitate was washed three times with acetone and dried to obtain the polymer modifier.

[0038] Example 2: A modified polymer binder for metallurgical pellets, comprising the following components in parts by weight: 60 parts sodium montmorillonite, 20 parts grafted modified sodium carboxymethyl cellulose, 5 parts corn starch, 5 parts sodium alginate, and 4 parts sodium humate.

[0039] The preparation method of the metallurgical pellet-specific modified polymer binder is as follows: the sodium-based montmorillonite, grafted modified sodium carboxymethyl cellulose, corn starch, sodium alginate and sodium humate are mixed evenly, and then dried, crushed and ground to obtain the metallurgical pellet-specific modified polymer binder.

[0040] The grafted modified sodium carboxymethyl cellulose is prepared through the following steps:

[0041] S1. Under nitrogen protection, 100g of sodium carboxymethyl cellulose was dispersed in 1000mL of N,N-dimethylformamide and stirred at room temperature for 2h. Then, 30g of 3-maleimide propionic acid, 35g of N,N-dicyclohexylcarbodiimide and 5g of 4-dimethylaminopyridine were added in sequence. The mixture was heated to 55℃ and reacted for 12h. The reaction solution was cooled to room temperature, filtered, and the filtrate was poured into anhydrous ethanol to precipitate. The precipitate was washed three times each with ethanol and water and dried to obtain sodium maleimide-modified carboxymethyl cellulose.

[0042] S2. Add 100g of maleimide-modified sodium carboxymethyl cellulose to 1500mL of N,N-dimethylformamide, then add 5g of ethylenediaminetetraacetic acid and 50g of polymer modifier. Adjust the pH to 7.0 with 0.1mol / L hydrochloric acid or 0.1mol / L sodium hydroxide solution, react for 24h, then remove the solvent, wash three times with ethanol, and dry to obtain the grafted modified sodium carboxymethyl cellulose.

[0043] The polymer modifier is prepared by the following steps:

[0044] (1) Dissolve 55g of 2-mercapto-1H-benzimidazole-5-carboxylic acid and 68g of cashew phenol in 600mL of tetrahydrofuran, add 2.5g of 4-dimethylaminopyridine and 30g of N,N-dicyclohexylcarbodiimide, react at 60℃ for 18h, filter to remove the precipitate, add 25g of bromohexane to the filtrate, heat to 80℃ and react for 36h, remove the solvent, recrystallize the residue three times with a mixed solution of ethyl acetate and n-hexane in a volume ratio of 1:3, and dry to obtain cashew phenol quaternary ammonium salt monomer;

[0045] (2) Using an oil-water separation device, 40g of hydroxyethyl methacrylate and 72g of oleanolic acid carboxypropyl ester were added to 350mL of toluene. After mixing evenly, 1.8g of p-toluenesulfonic acid and 0.5g of hydroquinone were added. The mixture was refluxed for 18h. The reaction solution was then cooled to room temperature. The organic phase was washed three times each with 5% sodium bicarbonate solution and deionized water to remove the solvent. After drying, the modified oleanolic acid monomer was obtained.

[0046] (3) Under nitrogen protection, 30g of cashew phenol quaternary ammonium salt monomer, 8g of oleanolic acid modified monomer and 30g of 3-acrylamidopropanesulfonic acid were added to 400mL of N,N-dimethylformamide, mixed evenly and then 1.5g of azobisisobutyronitrile was added. The reaction was carried out at 70℃ for 12h. The reaction solution was then cooled to room temperature and poured into acetone to precipitate. The precipitate was washed with acetone 3 times and dried to obtain the polymer modifier.

[0047] Example 3: A modified polymer binder for metallurgical pellets, comprising the following components in parts by weight: 55 parts sodium montmorillonite, 15 parts grafted modified sodium carboxymethyl cellulose, 4 parts corn starch, 4 parts sodium alginate, and 3 parts sodium humate.

[0048] The preparation method of the metallurgical pellet-specific modified polymer binder is as follows: the sodium-based montmorillonite, grafted modified sodium carboxymethyl cellulose, corn starch, sodium alginate and sodium humate are mixed evenly, and then dried, crushed and ground to obtain the metallurgical pellet-specific modified polymer binder.

[0049] The grafted modified sodium carboxymethyl cellulose is prepared through the following steps:

[0050] S1. Under nitrogen protection, 100g of sodium carboxymethyl cellulose was dispersed in 800mL of N,N-dimethylformamide and stirred at room temperature for 2h. Then, 25g of 3-maleimide propionic acid, 30g of N,N-dicyclohexylcarbodiimide and 3.5g of 4-dimethylaminopyridine were added in sequence. The mixture was heated to 53℃ and reacted for 12h. The reaction solution was cooled to room temperature, filtered, and the filtrate was poured into anhydrous ethanol to precipitate. The precipitate was washed three times each with ethanol and water and dried to obtain sodium maleimide-modified carboxymethyl cellulose.

[0051] S2. Add 100g of maleimide-modified sodium carboxymethyl cellulose to 1200mL of N,N-dimethylformamide, then add 3.5g of ethylenediaminetetraacetic acid and 40g of polymer modifier. Adjust the pH to 6.8 with 0.1mol / L hydrochloric acid or 0.1mol / L sodium hydroxide solution, react for 20h, then remove the solvent, wash three times with ethanol, and dry to obtain the grafted modified sodium carboxymethyl cellulose.

[0052] The polymer modifier is prepared by the following steps:

[0053] (1) Dissolve 55g of 2-mercapto-1H-benzimidazole-5-carboxylic acid and 65g of cashew phenol in 500mL of tetrahydrofuran, add 2.0g of 4-dimethylaminopyridine and 27g of N,N-dicyclohexylcarbodiimide, react at 55℃ for 15h, filter to remove the precipitate, add 22g of bromohexane to the filtrate, heat to 78℃ and react for 30h, remove the solvent, recrystallize the residue three times with a mixed solution of ethyl acetate and n-hexane in a volume ratio of 1:3, and dry to obtain cashew phenol quaternary ammonium salt monomer;

[0054] (2) Using an oil-water separation device, 40g of hydroxyethyl methacrylate and 68.5g of oleanolic acid carboxypropyl ester were added to 335mL of toluene. After mixing evenly, 1.65g of p-toluenesulfonic acid and 0.35g of hydroquinone were added. The mixture was refluxed for 15h. The reaction solution was then cooled to room temperature. The organic phase was washed three times each with 5% sodium bicarbonate solution and deionized water to remove the solvent. After drying, the oleanolic acid modified monomer was obtained.

[0055] (3) Under nitrogen protection, 30g of cashew phenol quaternary ammonium salt monomer, 5.5g of oleanolic acid modified monomer and 27.5g of 2-(methacryloyloxy)ethanesulfonic acid were added to 350mL of N,N-dimethylformamide, mixed evenly and then 1.35g of azobisisobutyronitrile was added. The reaction was carried out at 68℃ for 10h. The reaction solution was then cooled to room temperature and poured into acetone to precipitate. The precipitate was washed three times with acetone and dried to obtain the polymer modifier.

[0056] Example 4: A modified polymer binder for metallurgical pellets, characterized in that it comprises the following components in parts by weight: 50 parts sodium montmorillonite, 20 parts grafted modified sodium carboxymethyl cellulose, 3 parts corn starch, 3 parts sodium alginate, 2 parts sodium humate, and the rest are the same as in Example 3.

[0057] Example 5: A modified polymer binder for metallurgical pellets, characterized in that it comprises the following components in parts by weight: 55 parts sodium montmorillonite, 20 parts grafted modified sodium carboxymethyl cellulose, 4 parts corn starch, 4 parts sodium alginate, and 3 parts sodium humate, with the remainder being the same as in Example 3.

[0058] Example 6: A modified polymer binder for metallurgical pellets, characterized in that it comprises the following components in parts by weight: 60 parts sodium montmorillonite, 10 parts grafted modified sodium carboxymethyl cellulose, 5 parts corn starch, 5 parts sodium alginate, and 4 parts sodium humate, with the remainder being the same as in Example 3.

[0059] Comparative Example 1: The difference between this comparative example and Example 3 is that no cashew phenol quaternary ammonium salt monomer was added in the preparation of the polymer modifier, and all other aspects are the same as in Example 3.

[0060] Comparative Example 2: The difference between this comparative example and Example 3 is that no oleanolic acid modifying monomer was added in the preparation of the polymer modifier, and all other aspects are the same as in Example 3.

[0061] Comparative Example 3: The difference between this comparative example and Example 3 is that no sulfonic acid unsaturated monomer was added in the preparation of the polymer modifier, and all other aspects are the same as in Example 3.

[0062] Comparative Example 4: This comparative example differs from Example 3 in that the grafted modified sodium carboxymethyl cellulose is replaced with an equal amount of ordinary sodium carboxymethyl cellulose, while all other aspects are the same as in Example 3.

[0063] Results Analysis

[0064] The modified polymer binder for metallurgical pellets prepared in Examples 1-6 and Comparative Examples 1-4 of this invention was mixed with iron concentrate at an addition rate of 1% and then added to a pelletizing machine for pelletizing. The pellets were then tested according to GB / T 14201-2018 for drop strength (times / 0.5m) and compressive strength (N / pellet). The green pellets were heated to rupture at 10℃ / min and the bursting temperature was recorded. The calcined pellets (1250℃×15min) were cooled and the compressive strength (N / pellet) was tested according to ISO 4700. The pellet grade was also analyzed by XRF method.

[0065] Table 1 Comparison of Pellet Performance Parameters

[0066] serial number Drop strength of raw balls Compressive strength of green pellets Burst temperature Compressive strength of sintered balls Pellet quality Example 1 8.0 12.5 415 2850 65.02 Example 2 8.1 13.0 432 2880 65.11 Example 3 8.3 13.5 430 2820 65.27 Example 4 7.9 12.8 422 2880 65.42 Example 5 8.2 13.2 426 2850 65.18 Example 6 7.8 12.6 417 2870 65.25 Comparative Example 1 6.2 9.2 372 2580 64.05 Comparative Example 2 5.8 8.5 375 2530 63.88 Comparative Example 3 5.9 9.1 368 2480 63.53 Comparative Example 4 4.5 6.6 268 2380 63.28

[0067] As can be seen from Table 1, the pellets prepared by the embodiments of the present invention have better green pellet drop strength, green pellet compressive strength, calcined pellet compressive strength and pellet grade than the comparative example, and higher bursting strength than the comparative example. This indicates that the binder disclosed in the present invention can maintain the bonding force throughout the calcination process, reduce the strength loss caused by thermal degradation, and significantly improve the green pellet formability, transportation stability and high temperature crack resistance.

[0068] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0069] The present invention and its embodiments have been described above. This description is not restrictive, and the embodiments shown are only one of the embodiments of the present invention. The actual application is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A modified polymeric binder for metallurgical pelletizing, characterized in that: The composition includes the following components in parts by weight: 50-60 parts sodium montmorillonite, 10-20 parts grafted modified sodium carboxymethyl cellulose, 3-5 parts corn starch, 3-5 parts sodium alginate, and 2-4 parts sodium humate. The grafted modified sodium carboxymethyl cellulose is prepared by the following steps: S1. Under nitrogen protection, sodium carboxymethyl cellulose was dispersed in N,N-dimethylformamide and stirred at room temperature for 2 hours. Then, 3-maleimide propionic acid, N,N-dicyclohexylcarbodiimide and 4-dimethylaminopyridine were added in sequence. The mixture was heated to 50-55℃ and reacted for 12 hours. The reaction solution was cooled to room temperature, filtered, and the filtrate was poured into anhydrous ethanol to precipitate. The precipitate was washed three times each with ethanol and water and dried to obtain maleimide-modified sodium carboxymethyl cellulose. S2. Maleimide-modified sodium carboxymethyl cellulose is added to N,N-dimethylformamide, followed by ethylenediaminetetraacetic acid and a polymer modifier. The pH is adjusted to 6.5-7.0 with 0.1 mol / L hydrochloric acid or 0.1 mol / L sodium hydroxide solution. The reaction is carried out for 16-24 hours. Then the solvent is removed, the mixture is washed three times with ethanol, and dried to obtain the grafted modified sodium carboxymethyl cellulose.

2. The modified polymeric binder for metallurgical pelletizing according to claim 1, characterized in that: The polymer modifier is prepared by the following steps: (1) Dissolve 2-mercapto-1H-benzimidazole-5-carboxylic acid and cashew phenol in tetrahydrofuran, add 4-dimethylaminopyridine and N,N-dicyclohexylcarbodiimide, react at 50-60℃ for 12-18h, filter to remove the precipitate, add bromohexane to the filtrate, heat to 76-80℃ and react for 24-36h, remove the solvent, recrystallize the residue three times with a mixed solution of ethyl acetate and n-hexane in a volume ratio of 1:3, and dry to obtain cashew phenol quaternary ammonium salt monomer; (2) Using an oil-water separation device, hydroxyethyl methacrylate and carboxypropyl oleanolic acid were added to toluene, mixed evenly, and then p-toluenesulfonic acid and hydroquinone were added. The mixture was refluxed for 12-18 hours. The reaction solution was then cooled to room temperature. The organic phase was washed three times each with 5% sodium bicarbonate solution and deionized water to remove the solvent. After drying, the modified oleanolic acid monomer was obtained. (3) Under nitrogen protection, cashew phenol quaternary ammonium salt monomer, oleanolic acid modified monomer and sulfonic acid unsaturated monomer are added to N,N-dimethylformamide, mixed evenly and then azobisisobutyronitrile is added. The reaction is carried out at 65-70℃ for 8-12h. The reaction solution is then cooled to room temperature and poured into acetone to precipitate. The precipitate is washed with acetone 3 times and dried to obtain the polymer modifier.

3. The modified polymeric binder for metallurgical pelletizing according to claim 1, characterized in that: In step S1, the feeding ratio of sodium carboxymethyl cellulose, 3-maleimide propionic acid, N,N-dicyclohexylcarbodiimide, 4-dimethylaminopyridine and N,N-dimethylformamide is 100g: 20-30g: 25-35g: 2-5g: 600-1000mL.

4. The modified polymeric binder for metallurgical pelletizing according to claim 1, characterized in that: In step S1, the feeding ratio of maleimide-modified sodium carboxymethyl cellulose, ethylenediaminetetraacetic acid, polymer modifier, and N,N-dimethylformamide is 100g: 2-5g: 30-50g: 800-1500mL.

5. The modified polymeric binder for metallurgical pelletizing according to claim 2, characterized in that: In step (1), the feeding ratio of 2-mercapto-1H-benzimidazole-5-carboxylic acid, cashew phenol, 4-dimethylaminopyridine, N,N-dicyclohexylcarbodiimide, bromohexane and tetrahydrofuran is 55g: 62-68g: 1.5-2.5g: 25-30g: 20-25g: 400-600mL.

6. The modified polymeric binder for metallurgical pelletizing according to claim 2, characterized in that: In step (2), the feeding ratio of hydroxyethyl methacrylate, carboxypropyl oleanolic acid, p-toluenesulfonic acid, hydroquinone and toluene is 40g: 65-72g: 1.5-1.8g: 0.2-0.5g: 320-350mL.

7. The modified polymeric binder for metallurgical pelletizing according to claim 2, characterized in that: In step (3), the feeding ratio of cashew phenol quaternary ammonium salt monomer, oleanolic acid modified monomer, sulfonic acid unsaturated monomer, azobisisobutyronitrile and N,N-dimethylformamide is 30g: 3-8g: 25-30g: 1.2-1.5g: 300-400mL.

8. The modified polymeric binder for metallurgical pelletizing according to claim 2, characterized in that: The sulfonic acid unsaturated monomer is selected from one of 2-acrylamido-2-methylpropanesulfonic acid, 3-acrylamidopropanesulfonic acid, or 2-(methacryloyloxy)ethanesulfonic acid.

9. A method for preparing a modified polymeric binder for metallurgical pelletizing according to any one of claims 1-8, characterized in that: The sodium-based montmorillonite, grafted modified sodium carboxymethyl cellulose, corn starch, sodium alginate and sodium humate are mixed evenly, and then dried, crushed and ground to obtain the modified polymer binder for metallurgical pellets.